If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(y-4)-9=-1
We move all terms to the left:
6(y-4)-9-(-1)=0
We add all the numbers together, and all the variables
6(y-4)-8=0
We multiply parentheses
6y-24-8=0
We add all the numbers together, and all the variables
6y-32=0
We move all terms containing y to the left, all other terms to the right
6y=32
y=32/6
y=5+1/3
| -4r-1=-41 | | 4n+n+3=10+2n+8 | | 3z-11=13 | | 2k+10=148 | | 7-w=15/9 | | 9k-4-4K=26 | | 7–w=15.9 | | a-1/2=6 | | B=7/5(j-3) | | 5^5x+1=25^x+2 | | 19.2+r=33.7 | | 3x+2(-5)=-16 | | X-4=2x+5-7x | | 130=3x+130 | | 3+3(2-3x)=8-4(x-2) | | x=1/7+1/7 | | 7^x=345 | | 10x+18=−5x4x+11 | | 1/2w-15=-3 | | X2+32x+68=0 | | 3x=12x=-6 | | 15=n/3.7 | | 10=3^5+x | | n^{2}+3=4 | | -11=x/11-9 | | -3(x-6)=5(2x+3 | | G(2.5)=2x^2+3x+2 | | -3(6w-3)+7w=5(w+3) | | -92=16x-8-4 | | 4+2+-19+13+17+(5x-15)=7 | | -16x-12=4 | | 20+3x/4=29 |